ANTIBACTERIAL SUBSTANCE PRODUCED BY A SOIL BACTERIA ISOLATED FROM RHIZOSPHERE OF ZINGIBER OFFICINALE - SULISTYANI, NANIK; MURTI, YOSI BAYU; WIDADA, JAKA; MUSTOFA (International Journal of Applied Pharmaceutics, 2021)
Objective: In our previous study, we have found many isolates of bacteria from Zingiber officinale rhizosphere in Magelang, Central Java, Indonesia. J4, one of the isolates, has been found to contain metabolites which have antibacterial activity. The active chemical compound was unidentified. This study aims to identify the molecular formula of the active compound which has potential antibacterial activity. Methods: Identification of selected bacteria (J4 isolate) was based on the 16S rRNA gene sequence. Extraction of J4 isolate culture broth was carried out using ethyl acetate and followed by fractionation with hexane, chloroform-methanol (7:3), and methanol. The fraction which has antibacterial activity analyzed using IR Spectroscopy and LC-TOF-MS. Results: BLAST analysis result of the 16S rRNA sequence showed that J4 isolate is Burkholderia sp with 99% similarity. According to the IR spectroscopy examination of the active fraction, there were OH, CH, and carbonyl stretching. LC-TOF-MS analysis showed 5 molecular formulas with m/z of 253, 274, 387 (two formulas), and 404 in the active fraction, but there was one formula with no OH groups. Conclusion: J4 isolate is a Burkholderia sp. The molecular formula for the antibacterial substance that might be produced by J4 isolate is C6H12N12, C21H29N3O5, C21H26N2O5, C17H22N8O3, and/or C15H35N3O.